Pakistan and Afghanistan the (in)stability factor in India's neighbourhood - Chatterjee, Kingshuk (Institute of Foreign Policy Studies, Centre for Pakistan and West Asian Studies, Calcutta University in association with KW Publishers, New Delhi, 2013)
Theorising the war on terror / Shibasish Chatterjee and Shreya Maitra Roychoudhury -- Pakistan and Afghanistan: of instability and umbilical ties / Kingshuk Chatterjee -- Dragon splashing the muddy water: China in South Asian region / Binoda kumar Mishra -- India's Afghan policy: America's victory to Pakistan's quagmire / Pramit Palchaudhuri -- Urban vulnerabilities in 'post-conflict' Afghanistan / Arpita Basu Roy -- Pashtunwali and its impact on insurgency and reconciliation efforts in Afghanistan / Anwesha Ghosh -- Economic impact of terrorism: case of South Asia post 9/11 / Anindya Sengupta and Anshuman Tiwari -- Cinematic interpretations of terrorism-images, identity and impressions in Hindi cinema / Swati Bakshi